Tibial revision knee arthroplasty with metaphyseal sleeves: the effect of stems on implant fixation and bone flexibility - Nadorf, Jan; Kinkel, Stefan; Gantz, Simone; Jakubowitz, Eike; Kretzer, Jan Philippe (PLOS ONE, 2017)
Introduction Revision total knee arthoplasty often requires modular implants to treat bone defects of varying severity. In some cases, it may not be clear which module size and implant combination (e.g. sleeve and stem) should be chosen for a specific defect. When balancing implant stability and osseointegration against stress-shielding, it is important to choose an appropriate implant combination in order to match the given level of bone loss. Therefore, the necessity of stems in less extensive tibial defects and the advantage of different stems (lengths and stiffnesses) in combination with large metaphyseal sleeves on implant fixation and bone flexibility using a modular tibial revision knee system, were analyzed. Materials and methods Four different stem combinations for a tibial revision implant (Sigma TC3, DePuy) were compared to an intact bone. Standardized implantation with n = 4 synthetic tibial bones was performed after generating an Anderson Orthopaedic Research Institute (AORI) Type T1 bone defect. Axial torques around the longitudinal stem axis and varus-valgus torques were separately applied to the implant. Micromotions of bone and implant were tracked using a digital image correlation system to calculate relative micromotions at the implant-bone-interface and bone deformation. Results Overall, using stems reduced the proximal micromotions of tray and sleeve compared to no stem, while reducing bone deformation proximally at the same time, indicating some potential for proximal stress-shielding compared to no stem. The potential for increased proximal stress-shield due to reduced proximal deformation appeared to be greater when using the longer stems. The location of lowest relative micromotions was also more distal when using long stems as opposed to short stems. A short stem (especially a smaller diameter short stem which still achieves diaphyseal fixation) displayed less potential for stress-shielding, but greater bone deformation distal to the tip of the stem than in the natural model. Discussion In the case of tibial revision implants with metaphyseal sleeves in a simple fully contained Type I defect, the absence of a stem provides for more natural bone deformation. However, adding a stem reduces overall relative micromotions, while introducing some risk of proximal stress-shielding due to increased diaphyseal fixation. Increasing stem length intensifies this effect. Short stems offered a balance between reduced micromotions and more proximal bone deformation that reduced the potential for stress-shielding when compared to long stems. A short stem with slightly smaller diameter (simulating a less stiff stem which still has diaphyseal fixation) increased the proximal bone deformation, but also tended to increase the bone deformation even further at the distal stem’s tip. Conclusion In conclusion, further investigation should be conducted on fully contained Type I defects and the addition of a stem to offer better initial stability, taking into account stem length (i.e. shorter or more flexible stems) to support metaphyseal fixation and allowing bending found in intact bone. In addition, further study into more extensive tibial defects is required to determine if the stability/micromotion trends observed in this study with stems and sleeves in Type I defects still apply in cases of extensive proximal bone loss.